Maximizing Step‐Normalized Increases in Molecular Complexity: Formal [4+2+2+2] Photoinduced Cyclization Cascade to Access Polyheterocycles Possessing Privileged Substructures. Issue 4 (7th December 2021) - Reddy, D. Sai; Novitskiy, Ivan M.; Kutateladze, Andrei G.
Abstract: A new complexity building photoinduced cascade which amounts to an unprecedented formal [4+2+2+2] cycloaddition topology is developed to access complex nitrogen polyheterocycles. This photocascade is initiated by the excited state intramolecular proton transfer (ESIPT) in aromatic amino ketones with tethered dual unsaturated pendants, i.e. pyrrole and alkenic moieties, resulting in the formation of four σ‐bonds and setting six new stereogenic centers in a single experimentally simple photochemical step with up to 220 mcbit complexity increases. Abstract : Excited state intramolecular proton transfer (ESIPT) in aromatic o ‐amino ketones with tethered dual unsaturated pendants, i.e. pyrrole and alkenic moieties, initiates a complexity building photoinduced cascade of an unprecedented formal [4+2+2+2] topology, resulting in the formation of four σ‐bonds and setting six new stereogenic centers in a single photochemical step with up to 220 mcbit complexity increases.